Parallel computing on the road to exascale - Joubert, G. R. (Advances in parallel computing ;, 2016)
A number of innovative approaches to the development and use of future high-performance and high-throughput systems are to be found in this book, which will be of interest to all those whose work involves the handling and processing of large amounts of data.